2011
DOI: 10.1086/657631
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Prediction Rules for Methicillin-ResistantStaphylococcus aureusColonization

Abstract: We report electronic prediction rules that can fully automate triage of patients for MRSA-related hospital admission testing and that offer significant improvements on previously reported rules. The efficiencies introduced may result in savings to infection control programs with little sacrifice in effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
0
27
2
3
Order By: Relevance
“…Figure 2 can be used to determine the cost of a potential AST program. It is important to understand that if universal surveillance is the initial AST intervention, one will quickly learn the risk factors for colonization in one's own patient population, and then a prediction rule can be developed so that even though all patients are "screened (by a computer algorithm)" at admission, only a portion who are at higher risk actually need to be tested for MRSA colonization (23). This is noted in line B of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 can be used to determine the cost of a potential AST program. It is important to understand that if universal surveillance is the initial AST intervention, one will quickly learn the risk factors for colonization in one's own patient population, and then a prediction rule can be developed so that even though all patients are "screened (by a computer algorithm)" at admission, only a portion who are at higher risk actually need to be tested for MRSA colonization (23). This is noted in line B of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 where even though the table is constructed for 1,000 patients, only 500 are actually tested using a developed prediction rule. We implemented a prediction rule that was developed from our own universal surveillance program in January 2012 and now only test 50% of admissions, even though all are screened for MRSA risk using the prediction model (23). As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially, the predictive precision of clonotyping for resistance and clinical outcome could be improved by incorporating host factors into the algorithm, including demographic characteristics and comorbidity, as well as previous antibiotic treatment. Recent studies, for example, have demonstrated that electronic health records (EHRs) can be used to identify high-risk patients for targeted relapse prevention strategies directed toward other pathogens (9,23). Extensive genome-wide analysis of the predominant clonotypes is likely to yield additional and improved genetic markers for molecular diagnostics.…”
Section: Figmentioning
confidence: 99%
“…Within the EHR, data elements, including laboratory values, demographic data, medical history, infusional drug administration, and oral chemotherapy prescriptions, are stored in discrete structured fields and entered into a data warehouse. 3 The data warehouse is a clearinghouse for data from the clinical, laboratory, and billing systems for the institution in an Oracle-based platform. Our institution has a robust bioinformatics infrastructure with the ability to generate reports from the data warehouse by using Cognos software as a reporting tool that allows us to address both the process and outcomes of cancer care.…”
Section: Epic Ehr Impact On Quality and Researchmentioning
confidence: 99%